Peran Profitabilitas, Likuiditas, Aktivitas, dan Leverage dalam Harga Saham - Parmadi, Agus (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This research stems from the need to investigate the influence of financial factors, such as profitability, liquidity, activity, and leverage, on the share price of a company. The growing complexity of financial markets drives the need for a deeper understanding of the contribution of each factor to stock price dynamics. This research aims to identify and analyze the role of each financial factor of profitability, liquidity, activity and leverage in determining stock price movements. The research method used involves multivariable statistical analysis using historical financial data of companies listed on the stock market. This quantitative approach will help in dissecting the complex relationship between profitability, liquidity, activity, leverage, and stock price. This research produces significant findings regarding the impact of each financial factor on stock prices. An in-depth analysis will show to what extent profitability, liquidity, activity, and leverage influence a company's stock valuation. These results can be the basis for developing investment strategies that are smarter and responsive to market dynamics.